Respuesta :

Answer:

See below.

Step-by-step explanation:

These work just like ordinary algebraic expresssions, except you have to remember always:  i^2 = -1    i squared is negative one!

(4 - 3i)(4 + 3i)   "FOIL" the expression to get 16 - 3i + 3i - 9i^2.  But i^2 = -1, so this is the same as 16 - 3i + 3i + 9.  Combine like terms.

Ans. 25

(4 - 3i)(i)  Distribute the i to the two terms of the binomial.

4i - 3i^2 = 4i - 3(-1)

Ans. 4i + 3

(6i)(4 + 3i) = (6i)(4) + (6i)(3i) = 24i + 18i^2 = 24i + 18(-1)

Ans. 24i -18

(6i)(i) = 6i^2 = 6(-1)

Ans. -6

(-5)(4 + 3i) = -20 - 15i   That's it; there's no i^2 to deal with.

Ans. -20 - 15i

(-5)(i)   = -5i  Again, that's all there is to it.

Ans. -5i

ACCESS MORE